Three Biological Heresies - Skutch, Alexander F (Universidad de Costa Rica, 1996)
A science, like a religion, develops an orthodoxy, and those whose thought diverges from it become heretics. Although in the present age they are not likely to be bumt at the stake or forced by torture to recant, they can be penalized in various ways. Editors of scientific journals may reject their contributions; reviewers censure their books; universities are reluctant to give them professorships. Nevertheless, lhe scientific heretics of one age may become the revered pioneers of a laler age. Among the biological heresies of our day are anthropomorphism, teleology, and intergroup selection. Anthropomorphism makes unproved assumptions about the psychic life of animals. Teleology, the doctrine that nature strives toward predetermined ends or goals, is rejected because mutations are random and the agents of selection, chiefly predation, disease, starvation, and climatic extremes, care not at al1 for the welfare of a species. Intergroup selection is in disfavor because individuals, rather than families or groups, are primarily screened by natural selection. This essay presents three arguments on the aboye subjects. Current evolutionary theory is consistent with the idea that animals may have minds with varying degrees of similarity with the human mind. Careful anthropocentric interpretations of biological observations should not be rejected a priori. We should keep an open mind towards the possible existence of unconscious programmation towards an end, as known to exist in nucleic acid codification: much opposition to teleology is based on the inappropriate use of "purpose" and "end" as synonyms. Finally, the rejection of intergroup selection and the sole acceptance of individual selection in organic evolution is an oversimplification lhat neglects importan! phenomena such as coevolution and social interactions.